Chlorogenic Acid Protects Against Indomethacin-Induced Inflammation and Mucosa Damage by Decreasing Bacteroides-Derived LPS - Yan, Yongwang; Zhou, Xu; Guo, Kangxiao; Zhou, Feng; Yang, Hongqi (Frontiers in Immunology, 2020)
Background: Chlorogenic acid (CGA), as a nature bioactive polyphenol, exerts anti-inflammatory, antioxidant and antibacterial effects in the maintenance of intestinal health. However, the role of gut microbiota and their metabolites involved in the effects of CGA on the inflammatory bowel disease and related mechanisms remain to be elucidated. Methods: Here, we firstly used oral gavage to administer CGA in indomethacin-treated mice. Then fecal microbiota transplantation was performed to explore the role of intestinal microbiota in indomethacin-induced inflammation. Results: The results showed that CGA treatment protected against body weight loss, intestinal damage morphology and integrity, inflammation, and alteration of microbiota composition in indomethacin-treated mice. Interestingly, CGA failed to inhibit inflammation and to protect intestine integrity in antibiotics-treated mice. Notably, mice colonized with intestinal microbiota from CGA-treated or CGA- and indomethacin-treated mice, with the fecal microbiota transplantation program, were protected from indomethacin-induced inflammation, growth of Bacteroides and the accumulation of Bacteroides-derived LPS, as those treated with CGA did. Conclusion: Our results suggested that CGA may protect intestine integrity and alleviate inflammatory responses primarily by inhibiting the growth of Bacteroides and the accumulation of Bacteroides-derived LPS in indomethacin-induced colitis. This newly identified mechanism broadens our knowledge on how CGA exerts protective effects on intestine damage and provide strategies to prevent gastrointestinal mucosal damage for those patients administrated with indomethacin.